The muzykant as a product of nature and of culture - Przerembski, Zbigniew Jerzy (Interdisciplinary Studies in Musicology, 2018)
The article considers of the relations between nature and culture in reference to the traditional (folk) musician (‘muzykant’). His functions went beyond the strictly musical. Historical and ethnographical sources mention his supernatural abilities, his sacred and magical activities. He has been ascribed magical power, allowing him to influence the forces of nature and people’s health. The powers of him were believed to derive from his metaphysical practices and connection to nature. Some times he was accused of having links with demonic creatures. His ritual function, possibly taken over from the priests or shamans of pagan cults, endured in folk rites. In the rites of passage (during some family and annual ceremonies), in times of transition, places of crossing, traditional (folk) musician can take part in making a ritual din, believed as an effective manner against to demonic powers. It was a music awry, parody of music, eyen its inversion - a sort of ‘anti-music’, performed on ‘antiinstruments’, or on simple instruments.